Human intestinal mucosal mast cells: evaluation of fixation and staining techniques. Issue 8 (August 1981) - Strobel, S; Miller, H R; Ferguson, A
Abstract : The staining properties of tissue mast cells are influenced by the method of fixation. Differences in fixation and staining techniques may explain the contradictory results in the published reports on the number of human mucosal mast cells (MMC) in the gastrointestinal mucosa in health and disease. We have examined the influence of fixatives on the staining properties of human MMC in operative biopsy specimens of human jejunum. Specimens were divided into pieces, each of which was fixed in one of the following fixatives: Carnoy's, basic lead acetate (BLA), Baker's, Bouin's, isotonic formol-acetic-acid (IFAA), 10% neutral buffered formalin, formol sublimate, and formol saline. Thereafter, tissues were paraffin-embedded and 5 micron sections were cut and stained with either astra-blue/safranin pH 0.3, or toluidine blue pH 0.5. Counts of the number of MMC/mm2 were obtained for each fixation method. The results show a critical influence of the fixative on the number of mast cells identified after staining. For example with astra-blue/safranin the mean MMC/mm2 count was 40 in formol-saline-fixed specimens, and 268 in Carnoy's-fixed specimens. In biopsies fixed with formalin-based fixatives, mast cells were more readily stained with toluidine blue. It is recommended that Carnoy's or BLA be used as the fixative for any light microscopic study of human MMC.